2022
DOI: 10.2478/eces-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes and Abundance of Freshwater Snails in Anambra River (Nigeria) During the Rainy Season

Abstract: Rapid diversification is a way of responding to environmental change for freshwater organisms. This work examined the physicochemical changes and abundance of freshwater snails in Anambra River (Nigeria) during the rainy season. Field studies were conducted fortnightly from June to August 2019 at three stations of the river namely: Otuocha (station I), Otunsugbe (station II), and Ukwubili (station III) about 8.35 kilometers apart from each other. A scoop net of 2 cm mesh size and handpicking was used to sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Pearson correlation revealed no significant relationship between the water temperature and the abundance of snails throughout the season, with a significance level of 0.268 (P>0.05). This is in contrast to the findings of Okoye et al (2022) who recorded great abundance due to their endurance of a relatively high temperature. The high temperature recorded in this study can be attributed to the absence of shades in the Umoni and Adofi rivers, while in others there were partial shades.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Pearson correlation revealed no significant relationship between the water temperature and the abundance of snails throughout the season, with a significance level of 0.268 (P>0.05). This is in contrast to the findings of Okoye et al (2022) who recorded great abundance due to their endurance of a relatively high temperature. The high temperature recorded in this study can be attributed to the absence of shades in the Umoni and Adofi rivers, while in others there were partial shades.…”
Section: Discussioncontrasting
confidence: 99%
“…The significant contributions of organic matter in the water, which led to their greater mineralization, are what account for the high levels of electrical conductivity at the Ase River. This finding is in disagreement with Okoye et al (2022), in a similar study in the Anambra River (Nigeria) during the rainy season, who reported a low electrical conductivity range of 8.25 S/cm to 10.7 S/cm. Based on the study of Tchakonte et al (2014), increased electrical conductivity affects the maturity and survival of snails and increases their abundance.…”
Section: Discussioncontrasting
confidence: 98%
“…However, the pH values across the stations did not fall within the FMEnv recommended range of 6.50-8.50 for surface water. According to Enuneku et al [10] and Rim-Rukeh et al [11], acidic conditions in an aquatic body could be attributable to humic acid formed from decaying organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradation of NPs usually involves the release of certain extracellular enzymes (such as hydrolases) by microorganisms, which transforms complex NP polymers into low molecular forms through biodeterioration, bio-fragmentation, biosynthesis, and mineralization [ 166 , 207 ]. This process is influenced by biotic (metabolic activity, the release of acids, enzymatic activity) [ 208 , 209 ], abiotic factors (surface morphology, topography, surface hydrophobicity, electric charge distribution), and other environmental conditions (such as temperature, pH, salinity, oxygen level) [ 207 , 210 ].…”
Section: Remediation Strategies For Nanoplastic Surge In Africamentioning
confidence: 99%